Impact of a community-based health education intervention on awareness of influenza, pneumonia, and vaccination intention in chronic patients. Issue 1 (31st January 2022) - Chen, Yijuan; Gu, Weiling; He, Ben; Gao, Huijuan; Sun, Pinjing; Li, Qing; Chen, Enfu; Miao, Ziping
ABSTRACT: The study aimed to examine the impact of a community-based health education intervention on the awareness and attitude of influenza and Streptococcus pneumoniae vaccination in patients with chronic diseases. We selected study participants from two counties in Jiaxing City, Zhejiang Province. We conducted a household baseline survey with quarterly follow-up and health education for all chronic disease patients in the area. A total of 720 patients with chronic diseases were included in two rounds of questionnaire surveys before and after a year-long health education related to the influenza and Streptococcus pneumoniae vaccination. Before the community education, 59.9% and 59.6% of study participants self-report the awareness of the hazards of influenza and pneumonia, respectively; while only 17.7% and 6.0% study participants self-reported awareness of the influenza or pneumonia vaccination, respectively; the self-reported vaccination rates were 1.3% and 0% for influenza and pneumonia, respectively. One year after the intervention, all rates were increased significantly, but the influenza vaccination rate was still far below the WHO minimum target level (75%). The main reason for not getting vaccinated reported by study participants was that participants thought they were in good health and would not become sick easily. There was no statistically significant difference between the impacts of health care practitioners' and general practitioners' recommendations for vaccination. Continued and pertinent health education has a significant impact on influenza and pneumonia vaccination in patients with chronic diseases.